Effects of cast iron pipe corrosion on nitrogenous disinfection by-products formation in drinking water distribution systems via interaction among iron particles, biofilms, and chlorine. (April 2022) - Qi, Peng; Li, Tong; Hu, Chun; Li, Zesong; Bi, Zhihao; Chen, Youyi; Zhou, Huishan; Su, Ziliang; Li, Xinjun; Xing, Xueci; Chen, Chaoxiang
Abstract: The effects of cast iron pipe corrosion on nitrogenous disinfection by-products formation (N-DBPs) in drinking water distribution systems (DWDSs) were investigated. The results verified that in the effluent of corroded DWDSs simulated by annular reactors with corroded cast iron coupons, typical N-DBPs, including haloacetamides, halonitromethanes, and haloacetonitriles, increased significantly compared with the influent of DWDSs. In addition, more dissolved organic carbon, adenosine triphosphate, and iron particles were simultaneously detected in the bulk water of corroded DWDSs, thereby indicating that abundant iron particles acted as a "protective umbrella" for microorganisms. Under the condition of corroded DWDSs, the extracellular polymeric substances gradually exhibited distinct characteristics, including a higher content and lower flocculation efficiency, thereby resulting in a large supply of N-DBPs precursors. Corroded cast iron pipes, equivalent to a unique microbial interface, induced completely distinct microbial community structures and metabolic functions in DWDSs, thereby enhancing the formation of N-DBPs. This is the first study to successfully reveal the interactions among iron particles, biofilms, and chlorine in DWDSs, which may help to fully understand the biofilm transformation and microbial community succession in DWDSs. Graphical abstract: Image 1 Highlights: Effect of cast iron pipe corrosion on N-DBPs formation in simulated DWDSs was investigated. More N-DBPs, DOC, ATP and iron particles were detected in the bulk water of corroded DWDSs. Corroded cast iron pipes were equivalent to a unique microbial interface in DWDSs. The EPS characteristics of corroded DWDSs caused a large supply of N-DBPs precursors. The interaction among iron particles, biofilms, and chlorine in DWDSs significantly affected water quality stability.